2013
DOI: 10.1016/j.jmb.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Mechanism and Inhibition of the β-Hydroxydecanoyl-Acyl Carrier Protein Dehydratase from Pseudomonas aeruginosa

Abstract: Fatty acid biosynthesis is an essential component of metabolism in both eukaryotes and prokaryotes. The fatty acid biosynthetic pathway of Gram-negative bacteria is an established therapeutic target. Two homologous enzymes FabA and FabZ catalyze a key step in fatty acid biosynthesis; both dehydrate hydroxyacyl fatty acids that are coupled via a phosphopantetheine to an acyl carrier protein (ACP). The resulting trans-2-enoyl-ACP is further polymerized in a processive manner. FabA, however, carries out a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…The purified protein had an apparent monomeric molecular mass of ~18 kDa based on SDS-gel electrophoresis. The size exclusion chromatographic elution profile of FabQ (Figure S1 available online) indicated that the FabQ is a hexamer in solution form as are the FabZ proteins of E. coli and P. aeruginosa (Kimber et al, 2004), whereas the E. coli and P. aeruginosa FabA proteins are dimeric both in solution (Kass et al, 1967; Kimber et al, 2004) and in crystals (Leesong et al, 1996; Moynié et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified protein had an apparent monomeric molecular mass of ~18 kDa based on SDS-gel electrophoresis. The size exclusion chromatographic elution profile of FabQ (Figure S1 available online) indicated that the FabQ is a hexamer in solution form as are the FabZ proteins of E. coli and P. aeruginosa (Kimber et al, 2004), whereas the E. coli and P. aeruginosa FabA proteins are dimeric both in solution (Kass et al, 1967; Kimber et al, 2004) and in crystals (Leesong et al, 1996; Moynié et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Recently an unidentified anaerobic UFA synthesis mechanism involving a gene called ufaA was reported in Neiserria gonorrhoeae (Isabella and Clark, 2011), which may require a partner (perhaps a specific electron transport chain). Anaerobic synthesis of UFAs is unique to bacteria and thus the key enzymes of this pathway, particularly FabA, have been targeted for development of new antibacterial agents (Ishikawa et al, 2012; Moynié et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…[136] The NAC molecule hydrogen-bonds with loop C as well as with a water molecule bridging the other subunit. The NAC moiety binds closely to catalytic residues Asp84 and His70 (the same residues found in Ec FabA).…”
Section: Dehydratase (Dh)mentioning
confidence: 99%
“…Pa FabA and Ec FabA structures shows this loop contributes extensively to the alkyl-binding tunnel, whereas the α3-β3 loop is the major contributor to the alkyl-binding tunnel in FabZ. [136] …”
Section: Dehydratase (Dh)mentioning
confidence: 99%
See 1 more Smart Citation